Tourism in the Perspective of Islamic Fiqh - Arnoldy, Arnoldy; Hubur, Aa; Muqorobin, Ahmad (AL-IKTISAB: Journal of Islamic Economic Law, 2022)
••• English ••• Nowadays, halal tourism and tourism trends are increasingly in demand in the world. Seeing this potential, countries, both non-Muslim and Muslim countries, have relatively developed halal tourism. In the development of halal tourism, there is relatively no uniformity and consensus regarding halal tourism both in the world and in Indonesia, so that sometimes it confuses the actors in the tourism industry. This research aims to describe halal tourism activities in Islamic fiqh which is a conceptual review that uses qualitative research methods through literature study. This research results is, halal tourism is a segment of the world tourism market whose growth is good in line with the continued growth of the world's Muslim population, the number of a middle class in countries where the population is predominantly Muslim, and the number of world Muslim tourists. This potential causes many countries in the world to focus on serving this tourism segment, both Muslim and non-Muslim countries. Unfortunately, until now there is no uniformity and consensus regarding terms, terminology, content, and requirements for halal tourism both in the world and in Indonesia. Halal tourism standards adopted and used by Indonesia and several other countries in the world today relatively refer to the standards made by the Global Muslim Travel Index (GMTI), while the basic principles of fiqh in halal tourism in Indonesia are adopted from the Fatwa DSN-MUI No: 108/DSN-MUI/X/2016 concerning Guidelines for the Implementation of Tourism Based on Sharia Principles. ••• Indonesian ••• Saat ini wisata dan trend wisata halal semakin diminati di dunia. Melihat potensi itu membuat negara-negara baik negara non-Muslim maupun negara Muslim relatif sudah mengembangkan wisata halal. Dalam perkembangan wisata halal relatif belum terdapat keseragaman dan konsensus mengenai wisata halal baik di dunia maupun di Indonesia sehingga kadang membingungkan para pelaku dalam industri pariwisata. Penelitian ini bertujuan untuk mendeskripsikan kegiatan wisata halal dalam fiqh Islam yang merupakan tinjauan konseptual yang menggunakan metode penelitian kualitatif melalui studi pustaka. Hasil penelitian ini adalah, wisata halal merupakan segmen pasar pariwisata dunia yang pertumbuhannya baik sejalan dengan terus tumbuhnya populasi Muslim dunia, jumlah kelas menengah di negara-negara yang penduduknya mayoritas Muslim, dan jumlah wisatawan Muslim dunia. Potensi tersebut menyebabkan banyak negara di dunia fokus melayani segmen wisata ini, baik negara Muslim maupun non-Muslim. Sayangnya, sampai saat ini belum ada keseragaman dan kesepakatan mengenai istilah, terminologi, isi, dan persyaratan wisata halal baik di dunia maupun di Indonesia. Standar pariwisata halal yang dianut dan digunakan oleh Indonesia dan beberapa negara lain di dunia saat ini relatif mengacu pada standar yang dibuat oleh Global Muslim Travel Index (GMTI), sedangkan prinsip dasar fiqh dalam pariwisata halal di Indonesia diadopsi dari Fatwa DSN-MUI No: 108/DSN-MUI/X/2016 tentang Pedoman Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah.